WAGES OF THE TEACHER AS A FACTOR IN THE ECONOMIC SECURITY - M. Radosteva (Вестник университета, 2017)
The article discussed the problems related to the salaries of teachers in modern conditions. Presented teacher salary payment structure, the degree of satisfaction of the needs of Russian society as a basis for increasing wage. Teacher salary level is regarded as one of the factors that have a significant impact on the security of modern society.